1985
DOI: 10.1029/jb090ib08p06709
|View full text |Cite
|
Sign up to set email alerts
|

Heat flow in southernmost California and the origin of the Salton Trough

Abstract: Heat ftow in the Imperial Valley and adjacent crystalline rocks is very high ( -140 mW m -1 ). Gravity and seismic studies suggest the crust is about 23.5 km thick with the lower half composed of gabbro and the upper fourth composed of low-density sediments. Conduction through such a crust resting directly on asthenosphere would give the observed heat ftow if there were no extension or sedimentation. However, both processes must have been active, as the Imperial Valley is part of the Salton Trough, a pull-apar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
132
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(138 citation statements)
references
References 60 publications
6
132
0
Order By: Relevance
“…[39] The observed high heat flow values within the Salton Trough (see section 4.1.1) and Basin and Range province to the north suggest that lower crust composition within this region is likely to be gabbroic [Lachenbruch et al, 1985], and dry, to achieve the relative LC to UM strength contrast that our models imply [Afonso and Ranalli, 2004]. This model is at odds with the jelly sandwich model for mature continental lithosphere, which is characterized by a strong uppermost 19 to 1 Â 10 21 Pa s (see legend) over a given lower crust viscosity (horizontal labels beneath their respective model group).…”
Section: Lower Crust and Upper Mantle Structurementioning
confidence: 99%
See 2 more Smart Citations
“…[39] The observed high heat flow values within the Salton Trough (see section 4.1.1) and Basin and Range province to the north suggest that lower crust composition within this region is likely to be gabbroic [Lachenbruch et al, 1985], and dry, to achieve the relative LC to UM strength contrast that our models imply [Afonso and Ranalli, 2004]. This model is at odds with the jelly sandwich model for mature continental lithosphere, which is characterized by a strong uppermost 19 to 1 Â 10 21 Pa s (see legend) over a given lower crust viscosity (horizontal labels beneath their respective model group).…”
Section: Lower Crust and Upper Mantle Structurementioning
confidence: 99%
“…We did not test models in which the Salton Trough viscosity is greater than the adjacent crust, although it is unlikely that the decrease in m could be exactly compensated by increases in h. A higher viscosity would be inconsistent with the high heat flow values over the Salton Trough [Lachenbruch et al, 1985;Magistrale, 2002], that tend to suggest higher temperatures and lower viscosity at depth. However, it may be that sufficient material heterogeneity can increase (or maintain) viscosity despite increased temperatures [Thatcher and Pollitz, 2008].…”
Section: Salton Trough Lower Crustmentioning
confidence: 99%
See 1 more Smart Citation
“…Inland, Lachenbruch et al (1985) reported scattered locations of heat flows >100 mW/m 2 in San Bernardino County.…”
Section: Crustal Heat Flowmentioning
confidence: 99%
“…Their values are 1.5 -2 times higher than the average continental heat flows in the rest of the world. In general, the surface heat flows are contributed by basement, radiogenic elements, exhumation, burial, fault/fluid, magma, and tectonic components (Blackwell 1978;Bodell and Chapman 1982;Lachenbruch et al 1985;Armstrong and Chapman 1998). Understanding these components provides information for the regionally thermal regimes needed that reveal the thermal structure.…”
Section: The Silica Heat Flow Map Variation and Its Interpretationmentioning
confidence: 99%